Anna Barbauld’s Critique of Class Structures in Thoughts on the Inequality of Conditions - Lomonossoff, Natasha (Lumen, 2024)
Around the turn of the nineteenth century, British intellectuals continued to grapple with the discussions of class inequality that had been made more relevant with the occurrence of the French Revolution. Some writers believed that the poor as a group needed to be contained, so that they would not disrupt the wider structures of society. This essay examines a contribution to thinking on this subject by Anna Laetitia Barbauld in a pamphlet titled Thoughts on the Inequality of Conditions (1800). I explore how she advocates a more humanitarian approach to the condition of the poor, emphasizing the need to address the root causes of poverty. In contrast to figures such as Patrick Colquhoun and Hannah More, Barbauld offers proposals which would help lead to meaningful enfranchisement in the period.